2015
DOI: 10.1016/j.bbr.2014.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal engagement by cognitive reappraisal of negative faces

Abstract: Cognitive reappraisal has been associated with increased activation in prefrontal cortex (PFC) and cingulate regions implicated in cognitive control and affect regulation. To date, neuroimaging studies of reappraisal have primarily used emotionally evocative scenes, and it remains unclear whether the same cognitive strategy applied to emotional facial expressions would involve similar or different neural underpinnings. The present study used fMRI to examine brain activation during cognitive reappraisal of nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…29 Further, decreases in amygdala activation are not typically observed during expressive suppression. 26,30 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Further, decreases in amygdala activation are not typically observed during expressive suppression. 26,30 …”
Section: Introductionmentioning
confidence: 99%
“…Although suppression may have short-term benefits (Goldin, McRae, Ramel, & Gross, 2008), it does not diminish (and may even increase) physiological arousal (Gross, 1998;Klucken, Kruse, Schweckendiek, & Stark, 2015), can have negative social consequences (Spokas, Luterek, & Heimberg, 2009) and is linked to poor physical and psychological health (Musante & Treiber, 2000). Further, decreases in amygdala activation are not typically observed during expressive suppression (Goldin et al, 2008;Nelson et al, 2015).…”
mentioning
confidence: 99%
“…Emotional memory is considered to be closely linked to the areas such as the cingulum cortex, limbic system and so on [17][18][19]. Particularly, the influence of the amygdale and hypothalamus in the limbic system is most significant.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, individual differences in trait-level reappraisal have been associated with daily positive and negative emotional experiences (Gross and John, 2003). Neural evidence indicated that individuals with greater reappraisal scores tended to show decreased amygdala activity and increased medial prefrontal activity in response to angry and fearful faces (Drabant et al, 2009; Nelson et al, 2015). A previous neuroimaging study with a dot probe task revealed increased activity in the left amygdala as participants responded faster to the fearful faces presented on their left visual field (Carlson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…State and trait anxiety were also assessed. Based on the available evidence (Carlson et al, 2009; Drabant et al, 2009; Nelson et al, 2015), we hypothesized that the habitual tendency to use reappraisal to regulate emotions would be associated with slower orienting toward emotional faces.…”
Section: Introductionmentioning
confidence: 99%